Hydrogen-assisted failure in a bimodal twinning-induced plasticity steel: Delamination events and damage evolution. (25th January 2018) - Mohammadi, Abbas; Koyama, Motomichi; Gerstein, Gregory; Maier, Hans Jürgen; Noguchi, Hiroshi
Abstract: The effect of the bimodal grain size distribution on the hydrogen susceptibility of a high-Mn fully austenitic twinning-induced plasticity (TWIP) steel was investigated by tensile testing under ongoing electrochemical hydrogen charging. Observation of the surface microstructure of the hydrogen-charged specimen yielded a correlation between the microstructure, crack initiation sites, and crack propagation path. The observed embrittlement arose from crack initiation/propagation along the grain and twin boundaries and delamination governed crack growth. In the present bimodal TWIP steel, the fine grained regions mostly showed intergranular cracking along the grain boundaries between the fine and coarse grains. By contrast, the coarse grained region exhibited transgranular cracking along the twin boundaries. The delamination cracking phenomena is rationalized by the evident nucleation, growth, and coalescence of microvoids in the tensile direction. The results reveal that the bimodal grain size distribution of TWIP steel plays a major role in hydrogen-assisted cracking and the evolution of delamination-related damage. Highlights: Hydrogen embrittlement occurred in a bimodal-grained high-Mn fully austenitic TWIP steel. Grain boundary between fine and coarse grains acted as a crack initiation site. The presence of fine and coarse grains caused hydrogen-assisted crack delamination event. The delamination event occurs by plasticity-based mechanism, i.e. void coalescence.